The complete mitochondrial genome sequences of Bupleurum falcatum (Apiales: Apiaceae) - Chang-Kug Kim; Min-Woo Jin; Yong-Kab Kim (Mitochondrial DNA. Part B. Resources, 2020)
Bupleurum falcatum has a long history of use in traditional oriental medicine. The first complete mitochondrial genome sequences of B. falcatum were 463,792 bp based on 494,582 aligned reads. A total of 51 genes was annotated including 32 protein-coding genes, 16 tRNA genes, and three rRNA genes. In a comparison of B. falcatum and carrot (Daucus carota) revealed that the former species has four exclusive genes, but lacks six genes present in the latter. The compositional structure and phylogenetic relationships indicated that the mitochondrial genome of B. falcatum is similar to that of D. carota.